The Future of the surgeon-scientist: A Journey Funneled through inspiration, Roadblocks and Resilience. (February 2021) - Fanfan, Dino; Ehrlich, Haley; Elkbuli, Adel
Highlights: Declining financial opportunities along with clinical hour requirements to generate revenue produces role strains for surgeon-scientists. Adjusting the current workload model to include protected research time and devising financial support through partnerships can improve strain on surgeon-scientists. Early integration of research into medical education along with networking and mentorship can inspire future surgeon-scientists, potentially leading to positive career trajectories.